(untitled) (Вестник КазНУ. Серия Востоковедения, 2022)
In this article, the author revealed the history of the origin of the etiquette of “greeting” in the Kazakh and Chinese oral speaking language style, the level of the research and showed the types of forms of greeting, its linguocultural features. The article examines the language vocabulary used by the Kazakhs and Chinese in greetings, features and similarities of gestures, types and areas of application of “greetings”. It was also noted that the Kazakh-Chinese language communication is carried out in accordance with the established rules and principles of the country, and it is necessary to recognize the similarities and differences of the features of the language etiquette in the Kazakh and Chinese languages. Every nation has its own norms of speech in society according to its national level and customs. Speech is used taking into account not only the age and environment of the interlocutors, but also the traditions of the country. In inter-state relations, using speech etiquette without knowledge of the customs and traditions of that country may cause difficulties or resentment. Therefore, when establishing contacts with representatives of a country, it is important to be aware of the consciousness of the people living in that country. Correct use of speech etiquette or language by the interlocutor clearly shows the level of attitude and respect people have for each other. Kazakh and Chinese society was formed in ancient times. However, our study is based on the fact that the speech of the two peoples is based on the laws of nomadic and sedentary way of life, as well as on the transmission and continuation of traditions and customs of this period.